The tongue is mightier than the printing press? - Zachariah, Benjamin (Dve domovini, 2019)
The article is a set of reflections on the uses of oral history in a communicative endeav-our that succeeds very often in effacing the role of the interviewer even as the de-mands of self-reflexivity insist on centring that role. The author consider cases where there is neither a clearly defined interviewer nor interviewee, nor is there an attempt to write down experiences as history. Following this, it asks what can be told in or by oral histories when the communication that produces them seeks to recover other-wise inaccessible histories and memories, but must use languages of legitimation that often cannot speak clearly about those inaccessible histories and memories.
Keywords: collective memory; kolektivni spomin; legitimation; legitimiteta; oral history; pisanje; postvarjenje; pripoved; reification; reifikacija; ustna pričevanja; writing; zgodovinski viri